Improved spatial resolution by induced live cell and organelle swelling in hypotonic solutions - Jaiswal, Astha; Lorenz, Holger (Scientific reports, 2019)
Induced morphology changes of cells and organelles are by far the easiest way to determine precise protein sub-locations and organelle quantities in light microscopy. By using hypotonic solutions to swell mammalian cell organelles we demonstrate that precise membrane, lumen or matrix protein locations within the endoplasmic reticulum, Golgi and mitochondria can reliably be established. We also show the benefit of this approach for organelle quantifications, especially for clumped or intertwined organelles like peroxisomes and mitochondria. Since cell and organelle swelling is reversible, it can be applied to live cells for successive high-resolution analyses. Our approach outperforms many existing imaging modalities with respect to resolution, ease-of-use and cost-effectiveness without excluding any co-utilization with existing optical (super)resolution techniques.
Gesehen am 07.10.2019